2018
DOI: 10.1097/dss.0000000000001447
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Previously Treated Facial Capillary Malformations: Results of Single-Center Retrospective Objective 3-Dimensional Analysis of the Efficacy of Large Spot 532 nm Lasers

Abstract: A large spot 532 nm laser is effective in previously treated patients with facial CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
1
14
0
5
Order By: Relevance
“…Our study proved that the large spot 532 nm laser is effective in the treatment of neck and trunk PWS in Caucasian patients ( Figures 1 C–E ). Objectively measured rates of improvement were similar to those found for facial PWS [ 5 , 18 ]. In these earlier studies we found that in previously untreated facial PWS median GCEmax was 70.4%, which is similar to 69.9% found in the current study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our study proved that the large spot 532 nm laser is effective in the treatment of neck and trunk PWS in Caucasian patients ( Figures 1 C–E ). Objectively measured rates of improvement were similar to those found for facial PWS [ 5 , 18 ]. In these earlier studies we found that in previously untreated facial PWS median GCEmax was 70.4%, which is similar to 69.9% found in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…There are several types of devices available for PWS treatment, including pulse-dye laser (PDL), intense pulse light (IPL), small and large spot 532 nm KTP (potassium-titanyl-phosphate) laser, and 1064 nm neodymium-doped yttrium aluminum garnet (Nd:YAG) laser. Others such as alexandrite 755 nm or diode 800–983 nm lasers are less commonly used and argon, copper and krypton lasers are currently not recommended because of the poor safety-to-efficacy profile [ 5 ]. Recently photodynamic therapy (PDT) has shown promising results for the treatment of PWS in Chinese patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(kolejność przedstawionych laserów wg rosnącej długości fali generowanej przez urządzenia): 1) lasery KTP (potassium titanyl phosphate) i lasery diodowe emitujące fale o długości 532 nm; 2) lasery pulsacyjno-barwnikowe emitujące światło w zakresie 585-595 nm, 3) lasery aleksandrytowe emitujące fale o długości 755 nm; 4) lasery diodowe emitujące fale w zakresie od 800 do 940 nm; 5) lasery Nd:YAG (neodymowo-jagowe) emitujące fale o długości 1064 nm; ich wiązka może penetrować nawet na głębokość 3-3,5 mm; 6) generatory intensywnych pulsów światła (intense pulsed light -IPL; 500-1200 nm); Other devices are used less frequently or are mostly historical in nature (table 1) [5].…”
Section: Wprowadzenieunclassified
“…In time these lesions may become hypertrophic [69,70]. In the treatment of this type of lesions, the most effective are lasers emitting the wavelength of 595 nm, although recent studies show the high effectiveness of 532 nm lasers with a large spot in the population of patients with phototypes from I-III [5,13,[71][72][73]. When treating this type of lesions, one should take into account the necessity to perform about 7-10 treatment sessions with the interval between treatments reduced to 2-4 weeks for PDL treatments and a slightly longer time for 532 nm lasers.…”
Section: Vascular Malformationsmentioning
confidence: 99%